Kinerja Rumah Sakit Swasta dengan Pembayaran INA CBGs di Era Jaminan Kesehatan Nasional: Casemix, Casemix Index, Hospital Base Rate - Nurwahyuni, Atik; Setiawan, Ery (Jurnal Ekonomi Kesehatan Indonesia, 2019)
Private hospitals must monitor their performance using indicators commonly used in DRG payment systems: casemix, casemix index and hospital base rate. This study aims to analyze the performance of private hospitals including casemix, casemix index and hospital base rate. This cross sectional study was conducted with a sample of 7 hospitals selected purposively representing private hospital type B, C, and D in 6 provinces. Casemix and CMI RS are strongly influenced by the hospital capacity, which the hospitals class B have higher casemix and CMI than class C and D hospitals. There is a phenomenon, CMI in class C hospitals smaller than class D which is probably caused by coding accuracy. The completeness and accuracy of diagnosis and procedures coding predominating affect the casemix and CMI. Almost all hospitals have HBR which are higher than National HBR except RSC3. It definitely will trigger profit from the implementation of INA-CBGs. Hospitals should monitor casemix, CMI and HBR regularly. The Ministry of Health is expected to publish the Cost Weight and National HBR as well as the average of casemix and CMI according to class of hospital, for a benchmark by hospitals.